Analysis of an LED lighting circuit using a hybrid buck-boost converter with high gain - Kei Eguchi; Kyoka Kuwahara; Takaaki Ishibashi (Energy Reports, 2020)
In this paper, a hybrid buck-boost dc-dc converter and its analysis method are presented for LED lighting applications. Unlike existing LED driver circuits, the proposed driver circuit has a hybrid structure which consists of a buck-boost converter and a switched-capacitor (SC) step-up converter with flying capacitors. The features of the proposed driver are as follows: 1. High voltage gain provided by cascading two dc-dc converters, 2. Flexible LED current control using step-up/step-down conversion, and 3. Small volume offered by a single inductor structure. Concerning the proposed driver circuit, a simple equivalent circuit is derived by theoretical analysis. Furthermore, the characteristics of the proposed converter are revealed by simulation program with integrated circuit emphasis (SPICE) simulations and breadboard experiments. The results of simulation and experiment demonstrate the feasibility of the proposed driver circuit. The proposed driver circuit can achieve about 89% efficiency and -10~V output when the output load is 400~mW.
Keywords: 330; Buck-boost converters; Hybrid DC-DC converters; LED lighting applications; Step-up converters; Switched-capacitor techniques